Physiology and Molecular Biology of Psychrotrophic Fungi: An Insight - Das, T.; Nandy, S.; Pandey, D.K.; Al-Tawaha, A.R.; Nongdam, P.; Bursal, Ercan; Shekhawat, M.S. (Springer Nature, 2022)
Among other environmental parameters, the temperature is an important abiotic factor in which the diversity of spices reduces at the extremes, and moreover, only a few microorganisms become the main flora of that region. These extremophiles represented bacteria, archaea, fungi, and algae that are found in both aquatic and terrestrial cold and hot environments. Cold-tolerated microorganisms known as psychrotrophic or psychrotolerant found in the snow, ice, and rocks. They have a significant role in the ecology of that particular environment. Like other extremophilic fungi, psychrotrophic fungi get broad attention due to their potential to produce cold-adapted enzymes, which have importance in pharmaceutical and biotechnological fields. However, research data on psychrotrophic fungi are lacking. Physiological studies of psychrotrophic fungi based on nutrition, growth medium, pH requirement, and the interaction of fungi with environmental factors are significantly important for fungus to grow optimally on a larger scale. The molecular basis of psychrotrophic or psychrotolerant fungi is reviewed in terms of biochemical mechanisms in this chapter. Moreover, the physiological and molecular study gives us a brief idea about psychrotroph adaptation strategies to sustain in a low environmental condition. Therefore, in this chapter, we attempt to deliver psychrotroph physiological and molecular features in relationship with adaptation to low temperature. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2022.
Keywords: Cold Tolerant; Low Temperature; Psychrotolerant; Psychrotrophic Fungi